Antibody guided irradiation of brain glioma by arterial infusion of radioactive monoclonal antibody against epidermal growth factor receptor and blood group A antigen. Issue 6480 (18th May 1985) - Epenetos, A A; Courtenay-Luck, N; Pickering, D; Hooker, G; Durbin, H; Lavender, J P; McKenzie, C G
Abstract : In a patient with recurrent grade IV glioma of the brain resistant to conventional treatment an antibody guided isotopic scan showed uptake by the tumour of a monoclonal antibody (9A) that was developed against epidermal growth factor receptor but cross reacted with blood group A antigen. As a therapeutic attempt antibody labelled with 1665 MBq (45.0 mCi) iodine-131 was delivered to the tumour area by infusion into the internal carotid artery. Computed tomography showed regression of the tumour after treatment, and an appreciable and sustained clinical improvement was noted without any toxicity. Delivery of irradiation guided by monoclonal antibody delivered by arterial infusion of the tumour area may be of clinical value in the treatment of brain gliomas resistant to conventional forms of treatment.